2007
DOI: 10.1161/atvbaha.107.148403
|View full text |Cite
|
Sign up to set email alerts
|

Wild-Type ApoA-I and the Milano Variant Have Similar Abilities to Stimulate Cellular Lipid Mobilization and Efflux

Abstract: Objective-The present study is a comparative investigation of cellular lipid mobilization and efflux to lipid-free human apoA-I and apoA-I Milano , reconstituted high-density lipoprotein (rHDL) particles containing these proteins and serum isolated from mice expressing human apoA-I or apoA-I Milano . Methods and Results-Cholesterol and phospholipid efflux to these acceptors was measured in cell systems designed to assess the contributions of ATP-binding cassette A1 (ABCA1), scavenger receptor type BI (SRBI), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 57 publications
2
28
0
Order By: Relevance
“…They also found that reconstituted HDL containing one molecule of dimeric apoA-IM was as equally potent as similarly sized (8 nm) particles containing two molecules of wild-type apoA-I in stimulating ABCA1-mediated effl ux from J774 macrophages. In agreement with that, Weibel et al ( 50 ) found no intrinsic difference in cholesterol effl ux capacities between apoA-IM and wild-type apoA-I in reconstituted HDL particles or in HDL isolated from wild-type or apoA-IM-expressing mice.…”
Section: Limitationssupporting
confidence: 88%
“…They also found that reconstituted HDL containing one molecule of dimeric apoA-IM was as equally potent as similarly sized (8 nm) particles containing two molecules of wild-type apoA-I in stimulating ABCA1-mediated effl ux from J774 macrophages. In agreement with that, Weibel et al ( 50 ) found no intrinsic difference in cholesterol effl ux capacities between apoA-IM and wild-type apoA-I in reconstituted HDL particles or in HDL isolated from wild-type or apoA-IM-expressing mice.…”
Section: Limitationssupporting
confidence: 88%
“…This has led some to believe that apoA-I Milano is more atheroprotective than normal apoA-I, (165) but one may also interpret this as evidence that HDL does not protect. Although this specifi c apoA-I mutation has been reported to induce enhanced cellular cholesterol effl ux compared with wild-type apoA-I (165) , others have disputed this (166).…”
Section: Cetpmentioning
confidence: 99%
“…Intervention studies in animal models have demonstrated that direct infusion of HDL-like particle or transgenic expression of its major proteins has a favorable impact on the extent and histologic phenotype of experimental atherosclerosis (11)(12)(13). Small studies in human have indicated favorable effects of HDL-like particle infusion on endothelial function and atherosclerosis (14)(15)(16)(17).…”
Section: Original Articlementioning
confidence: 99%
“…At least to date, these findings suggest that raising HDL-C may not be sufficient to further reduce cardiovascular risk in statin-treated patients. In contrast, favorable effects of infusing delipidated forms of HDL on lipid transporting factors, endothelial function and atherosclerotic plaque volume (14)(15)(16)(17) suggest that administering an engineered HDL particle, as opposed to indirectly altering its production or remodelling, might provide a more effective therapeutic approach. This would be consistent with recent reports that increasing the number of HDL particles, as opposed to HDL-C, may be more relevant to reducing cardiovascular risk (24).…”
Section: Original Articlementioning
confidence: 99%